Faktor-Faktor yang Mempengaruhi Ketaatan Minum Obat pada Penyakit Kronik - Maula Al Farisi (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Adherence is a key factor related to the effectiveness of all pharmacological therapies. Non-compliance with treatment is a significant barrier to achieving positive health outcomes especially for patients suffering from chronic diseases. Improving medication adherence is a public health priority and can reduce the economic and health burden. The purpose of this study is to assess treatment compliance with several common chronic diseases. There are many challenges in understanding the reasons for non-compliance. The main component in the management of patients with chronic health problems is the assessment of their adherence to therapeutic regimens. Low levels of patient adherence to therapeutic effectiveness have been associated with increased adverse health risks, increased spending on health care through hospitals and hospital care, lower quality of life, and higher rates of death. In this study treatment adherence to chronic diseases found suboptimal and is associated with socio-demographic characteristics of patients. Patient-adjusted interventions are needed to achieve adequate adherence to therapeutic drug regimens. The good outcome of chronic illness depends greatly on the level of patient compliance with treatment. Many studies have shown that some degree of non-compliance occurs universally, in rich and poor countries, and is even seen in life-threatening diseases.